Risk analysis and production dynamics of smallholder pig farming in rural areas of North Sulawesi - Santa, Nansi Margret; Rorimpandey, Boyke; Lainawa, Jolyanis; Wantasen, Erwin; Subagja, Hariadi (Jurnal Ilmu Peternakan Terapan, 2025)
Smallholder pig farming in rural areas of North Sulawesi important role in food security, household economy, and socio-cultural of local communities. However, this sector faces various risks. The aims to analyze production dynamics and identify risk factors that affect the sustainability of smallholder pig farming in rural areas. The research employed a quantitative approach through a survey of 604 farmers (having 3-4 sows/farmer). Data analyzed using multiple linear regression. The results showed that labor, the cage area, quantity of medicines, farm model, and farm location in rural areas significantly influenced pig production. The breeding model resulted in higher production than the combined pig farming model and tended to have lower production risks. Pig production in rural areas is also higher than in suburban areas. Disease risk is the main cause of losses, with production and income declines reaching 182.9% in the breeding model and 303.4% in the combined model. In conclusion, the breeding model resulted in higher production and tends to have lower production risks, particularly disease-related risks that directly affect productivity and farm continuity. These risks significantly reduce household production and income, highlighting the strong relationship between production dynamics, risk levels, and the economic stability of rural pig farmers.